2014
DOI: 10.1117/12.2040986
|View full text |Cite
|
Sign up to set email alerts
|

Methods for slow axis beam quality improvement of high power broad area diode lasers

Abstract: For high brightness direct diode laser systems, it is of fundamental importance to improve the slow axis beam quality of the incorporated laser diodes regardless what beam combining technology is applied. To further advance our products in terms of increased brightness at a high power level, we must optimize the slow axis beam quality despite the far field blooming at high current levels. The later is caused predominantly by the built-in index step in combination with the thermal lens effect. Most of the metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
1
1
0
Order By: Relevance
“…19,20) In addition, the fabricated grooves (Regions III and V) will also increase the losses of high-order lateral modes and reduce the number of lasing modes. 14) As expected, a narrower range of NF intensity of the LLGS laser can be obtained, as shown in the inset of Fig. 2.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…19,20) In addition, the fabricated grooves (Regions III and V) will also increase the losses of high-order lateral modes and reduce the number of lasing modes. 14) As expected, a narrower range of NF intensity of the LLGS laser can be obtained, as shown in the inset of Fig. 2.…”
supporting
confidence: 81%
“…However, there is still much room for the improvement of both the lateral beam quality and the output power of PBC BA lasers. It had been demonstrated that the control of the lateral index difference 14) and the suppression of carrier accumulation at the device edges 15) play an important role in the improvement of lateral beam quality. In this work, a ladderlike groove structure (LLGS) was introduced to BA PBC lasers to improve both the beam quality and the output power by reducing current diffusion and modifying the lateral index difference.…”
mentioning
confidence: 99%